SERBIA: MULTIVECTORNESS AS A WAY OUT OF THE IMPASS OF STRATEGIC VULNERABILITY - E. G. Ponomareva; M. Mladenovic (Сравнительная политика, 2020)
The Balkans remain a zone of strategic vulnerability. The aggravation of the latter has been defi ned by the struggle of the leading actors of world politics for the southern European country which has been for the time being relatively neutral in political and military senses, i.e. Serbia. Despite serious upheavals of the turn of the twenty-fi rst century (the destruction of Yugoslavia, NATO bombings, the “divorce” with Montenegro and the creation of the “Republic of Kosovo”) Belgrade has been managing to balance between two major poles of attraction – EU-NATO and Russia, which fi ts into the concept of multivectorness. Given all geographic, historical, cultural and economic predetermination of European integration its fi nal choice by Serbia is burdened by two essentially important moments – the need to recognize the “Republic of Kosovo” and the inclusion in the military and political framework of the NATO. Moreover, the fi rst issue brings substantial political and civilizational risks both for the Western Balkans and the whole of the European Union, let alone a serious internal split of the Serbian society in relation to the possibility of recognizing the Albanian new formation. A natural counterweight to the Euro-Atlanticist pressure on Belgrade is Russia which has unique image possibilities and unlike the EU does not pretend to play the role of an “empire by invitation”. The situation becomes more complicated by the fact that the existing historical dualism of multivectorness is being disrupted by the emergence in the Balkans of a new player – China. By solely economic levers Beijing has been solving strategic problems of penetration to European markets and simultaneously smoothly, but sequentially has been superseding Russia as Serbia’s main alternative of the West. Analyzing the tactics of the economic measures of Chinese companies the article concludes that there has been growing a concealed competition between the People's Republic of China and the Russian Federation for the place of the main nonEuropean actor not only in Serbia, but in the Balkans as a whole. In such circumstances the preservation of the policy of multivectorness (despite all criticism of the concept) can serve Serbia as the way out of the impasse of strategic vulnerability, i.e. to preserve in the short-term the prospect of the status quo of political, military and strategic neutrality.